2014
DOI: 10.1016/j.jmig.2013.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Lymphadenectomy in Locally Advanced Cervical Cancer Study (LiLACS): Phase III Clinical Trial Comparing Surgical With Radiologic Staging in Patients With Stages IB2–IVA Cervical Cancer

Abstract: Radiation treatment planning for women with locally advanced cervical cancer (stages IB2-IVA) is often based on positron emission tomography (PET). PET, however, has poor sensitivity in detecting metastases in aortocaval nodes. We have initiated a study that aims to determine if pretherapeutic laparoscopic surgical staging followed by tailored chemoradiation improves survival compared to PET/CT radiologic staging alone followed by chemoradiation. This international, multicenter phase III trial will enroll 600 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(48 citation statements)
references
References 25 publications
(37 reference statements)
1
43
0
Order By: Relevance
“…A definitive answer about the value of PET-CT in patients suffering from locally advanced cervical cancer will be provided at the completion of a prospective randomized trial, Lymphadenectomy in Locally Advanced Cervical Cancer Study, which is currently recruiting participants. 29 At present, only surgical staging allows the accurate evaluation of the most important prognostic and therapeutic factors in patients with locally advanced cervical cancer, including peritoneal spread, lymph node involvement, and tumor spread into adjacent organs. 12 Benedetti Panici et al 30 demonstrated a significant association between tumor stage and peritoneal spread in a retrospective study of 162 patients with locally advanced cervical cancer.…”
Section: Commentmentioning
confidence: 99%
“…A definitive answer about the value of PET-CT in patients suffering from locally advanced cervical cancer will be provided at the completion of a prospective randomized trial, Lymphadenectomy in Locally Advanced Cervical Cancer Study, which is currently recruiting participants. 29 At present, only surgical staging allows the accurate evaluation of the most important prognostic and therapeutic factors in patients with locally advanced cervical cancer, including peritoneal spread, lymph node involvement, and tumor spread into adjacent organs. 12 Benedetti Panici et al 30 demonstrated a significant association between tumor stage and peritoneal spread in a retrospective study of 162 patients with locally advanced cervical cancer.…”
Section: Commentmentioning
confidence: 99%
“…To the author's knowledge, there is no strong evidence at this moment on the survival benefit of the para-aortic lymphadenectomy that increases the survival; however, there are retrospective studies that showed better oncological results in patients who underwent lymphadenectomy compared to patients' assessment with imaging test [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Although the Federation of Gynecology and Obstetrics (FIGO) classification [1] does not include the assessment of para-aortic region, the presence of positive para-aortic lymph nodes remains the most important prognostic factor for survival in pa- Hernandez tients with cervical cancer [2,3]. In addition, the presence or absence of lymph node metastases leads to change of the treatment, from primary surgery to chemoradiation therapy.…”
Section: Introductionmentioning
confidence: 99%
“…A randomized trial is needed to resolve these questions. The multicenter international study LiLACS (Lymphadenectomy in Locally Advanced Cervical Cancer) directed by Frumovitz at MD Anderson [9], is a phase 3 clinical trial comparing surgical tailored chemoradiation versus PET/CT tailored chemoradiation, with…”
Section: Nodal Status and Rt Treatmentmentioning
confidence: 99%